2012
DOI: 10.5367/ihe.2012.0106
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap: Preparing Computing Students for Employment through Embedding Work-Related Learning in the Taught Curriculum

Abstract: This paper presents the findings from a pilot study which explored the impact of embedding work-related learning activities in the first-year computing curriculum at Glasgow Caledonian University. Students worked in teams on practical projects which were formally assessed and the researchers gathered student feedback using two online surveys (n=159) and focus groups (n=29). The findings indicate that 85% of the students felt that their learning on the module had improved their employability skills but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Although the intention of the value-adding events was to benefit all students, not just those who secured a placement, the preplacement preparation events had no impact on the students' sense of self as a professional. McKinnon & McCrae (2012) found that students had less confidence in their skills and abilities on completion of a work-related module with speculation that this was due to greater awareness of the challenges that lay ahead. Evidence elsewhere points to the importance of embedding meaningful employability activity in a discipline specific way (Oliver, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the intention of the value-adding events was to benefit all students, not just those who secured a placement, the preplacement preparation events had no impact on the students' sense of self as a professional. McKinnon & McCrae (2012) found that students had less confidence in their skills and abilities on completion of a work-related module with speculation that this was due to greater awareness of the challenges that lay ahead. Evidence elsewhere points to the importance of embedding meaningful employability activity in a discipline specific way (Oliver, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These programmes, such as internship, artisanship, placements and other work-based opportunities, are believed to provide students with valuable experience and skills (Lowden et al, 2011). Studies reviewed reveal that participants in graduate employment preparation programmes reported positive experiences with these, citing the benefits of having undergone such training (Lowden et al, 2011;McKinnon and Wood, 2012). According to these authors, the employers too reported satisfaction with the skills expected of the new graduate intake so much that some expressed that they reportedly appreciated the knowledge transfer opportunity and valued their work with the students as a useful recruitment tool.…”
Section: Graduate Employment Preparationmentioning
confidence: 99%
“…Studies reviewed reveal that participants in graduate employment preparation programmes reported positive experiences with these, citing the benefits of having undergone such training (Lowden et al, 2011;McKinnon and Wood, 2012). According to these authors, the employers too reported satisfaction with the skills expected of the new graduate intake so much that some expressed that they reportedly appreciated the knowledge transfer opportunity and valued their work with the students as a useful recruitment tool.…”
Section: Graduate Employment Preparationmentioning
confidence: 99%